Audiovisual translation theoretical and methodological challenges - Gambier, Yves, 1949-; Pinto, Sara Ramos (Benjamins current topics, 2018)
"The exponential growth of Audiovisual Translation (AVT) in the last three decades has consolidated its place as an area of study within Translation Studies (TS). However, AVT is still a young domain currently exploring a number of different lines of inquiry without a specific methodological and theoretical framework. This volume discusses the advantages and drawbacks of ten approaches to AVT and highlights the potential avenues opened up by new methods. Our aim is to jumpstart the discussion on the (in)adequacy of the methodologies imported from other disciplines and the need (or not) for a conceptual apparatus and framework of analysis specific to AVT. This collective work relates to recent edited volumes that seek to take stock on research in AVT, but it distinguishes itself from those publications by promoting links in what is now a very fragmented field"--